Fatal Postpartum Hemorrhage in Diffuse Midline Glioma with H3-K27M Mutation - Takeshi Miyazaki; Masahiro Tsuji; Shinya Hagiwara; Toshiko Minamoto; Noriyoshi Ishikawa; Junko Hirato; Sumihito Nobusawa; Yasuhiko Akiyama (Case Reports in Obstetrics and Gynecology)
Management of pregnant women with brain tumors necessitates difficult decision-making especially for estimating or preventing its intratumoral hemorrhage. A 26-year-old, 19-week pregnant woman complaining of headache and vomiting was admitted to our hospital. Magnetic resonance imaging (MRI) revealed hydrocephalus and a mass lesion without contrast enhancement extending from the left thalamus. To resolve severe symptoms, a ventriculoperitoneal shunt was inserted, and a biopsy was taken via the right ventricle. Pathological examination suggested diffuse or pilocytic astrocytoma, but subsequent genetic analysis revealed the diagnosis of midline glioma with H3-K27M mutation. The patient opted not to terminate the pregnancy, and MRIs conducted every four weeks revealed no change in tumor aspect. The patient delivered a healthy baby by cesarean section, and postpartum day 1 was uneventful. However, she was found in a coma due to a massive intratumoral hemorrhage on postpartum day 2 and died 3 weeks after the hemorrhage. This is the first case report of diffuse midline glioma with H3-K27M mutation in a pregnant woman followed by fatal hemorrhage. It highlights the necessity of careful clinical management and frequent neuroimaging during the entire perinatal period, even if the tumor has hypovascularity or low proliferative potential on radiological or pathological findings.